Structural and Electrical Properties of Ca2+ Doped LaFeO3: The Effect of A-site Cation Size Mismatch - Irmak, A. E. (Engineering, Technology & Applied Science Research, 2020)
In this study, nanosized La1-xCaxFeO3 (0.00≤x≤0.40) compounds prepared via sol-gel method followed by heat treatment at 1100oC for 24 hours are studied. Crystal structure, microstructure, surface morphology and temperature-dependent resistivity of the samples are investigated. TEM investigation reveals nanoparticles with an average size of 35nm produced from the sol-gel process. The crystal structure of the compounds belongs to an orthorhombically distorted perovskite structure with Pbnm space group. Lattice distortion and cation size mismatch increase with an increase in Ca and particle and grain growth are suppressed by Ca doping. Electrical conduction is explained via thermally activated hopping of small polarons. Unit cell volume, charge ordering temperature, and activation energy for small polarons decrease linearly with an increase in cation size mismatch. Room temperature resistivity decreases with Ca doping and gets its minimum value for 30% Ca at which the orthorhombic distortion is maximum.